Sensory Receptors Associated with the Labial Tip and Precibarium of Philaenus spumarius L. (Hemiptera: Aphrophoride). (February 2020) - Ranieri, Emanuele; Ruschioni, Sara; Riolo, Paola; Isidoro, Nunzio; Romani, Roberto
Abstract: The meadow spittlebug, Philaenus spumarius (Linnaeus) (Hemiptera: Aphrophoridae), is an important vector for the xylem-limited bacterium Xylella fastidiosa (Wells, Raju, Hung, Weisburg, Mandelco-Paul, and Brenner), which is associated with olive quick decline syndrome in southern Italy. The mouthparts of Hemiptera have important roles in host plant selection, feeding behavior and for vectoring pathogens that cause plant diseases. In this study, the functional morphology of the sensory structures located on the labium tip and precibarium of P . spumarius was investigated using scanning and transmission electron microscopy. The labium tip is composed of two symmetrical sensory complexes, each with five different types of sensilla: aporous sensilla trichodea type 1 and 2; uniporous sensilla chaetica type 1 and 2; and multiporous sensilla basiconica. The precibarium of P . spumarius has two kinds of sensory structures: bulbous sensilla and papillae sensilla. In particular, two groups of sensilla are located on the epipharynx: a distal group that consists of ten papillae sensilla and a proximal group composed of six papillae sensilla and two bulbous sensilla, while the hypopharynx has only two papillae sensilla. The involvement of these sensory structures in the context of feeding behavior and pathogen transmission is discussed.